Accuracy of Focused Assessment with Sonography for Trauma Performed by Emergency Medicine Residents - Rafia Shoukat, Muhammad Kashaf Naseer, Sumbal Shabbir, Hina Javed, Hafiz Muhammad Sajid Jehangir, Tanveer Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the accuracy of focused assessment with sonography for trauma (FAST) performed by emergency medicine residents to detect intra-peritoneal free fluid in blunt trauma patients. Design: Randomized control trial. Place and duration of study: Accident & Emergency Department, Mayo Hospital Lahore from 6th April 2022 to 5th November 2022. Methodology: One hundred and twenty one patients were included. FAST scan was performed in each patient by emergency resident as well as radiology resident. FAST was performed under direct supervision of radiology consultant. Furthermore, FAST reports were confirmed by patient follow up in first 24 hours by checking final outcome of patient based on results of abdominal computed tomography (CT), exploratory laparotomy or conservative management by admitting in surgical ward for observation and hemodynamic status change. Results: Focused assessment with sonography for trauma scan done by emergency residents showed free fluid in 20 patients (16.5%) while FAST done by radiology residents was positive in 21 (17.4%). Sensitivity of FAST performed by EM residents was 85.7% and specificity was 98%, while FAST done by radiology residents had sensitivity of 95.25 and specificity of 99%. Accuracy of FAST done by EM residents was 95.8% as final outcome. Conclusion: After training, emergency residents can perform FAST with high accuracy, similar to radiology residents in blunt abdominal trauma patients. Keywords: Focused assessment with sonography for trauma (FAST), Trauma, Blunt abdominal trauma